PROCEDURE OF QUANTITATIVE DETERMINATION OF THE TOTAL FLAVONOID CONTENT IN THE UNIFLOROUS VIOLET - A. M. Martynov (Scientific Сentre for Family Health and Human Reproduction Problems, 2017)
The object of the study was the aerial part of flowered violet (Viola uniflora L.), harvested at flowering time in the Irkutsk region. The herb contains flavonoids, phenolic acids, coumarins, tannins, polysaccharides, fatty acids and amino acids, as well as macro- and microelements. During the development of methods of quantitative determination of flavonoid compounds we experimentally established optimum conditions for their extraction from vegetable raw materials: the degree of grinding - 2 mm, extractant - 70% ethyl alcohol, the ratio of raw material - extractant 1:50 total extraction duration -1 hour (twice), time complexation reaction with a 5% ethanolic solution of aluminum chloride is 30 minutes. Stability of the complex was maintained for 1.5 hours. Quantitation of flavonoid compounds in the raw material were determined by differential spectrophotometry based on rutin. The optical density of the solution was measured on a recording spectrophotometer "Lambda 35 UV/VIS" Perkin Elmer instruments (USA) at a wavelength of 409 ± 2 nm in a cell with a working thickness of 10 mm. The content of flavonoids in terms of rutin in different samples ranged from 1.66 to 2.03 %. The developed method of quantitative spectrophotometric determination of the amount of flavonoids in Viola uniflora grass validated in terms of specificity, precision (convergence), linearity, accuracy and set its range of applications. According to the results of validation techniques quantification procedure of flavonoids Viola uniflora grass it has been found that the technique is reproducible and can be used in quantitative analysis.